Ngwaga wa Mopedi: seka sa ngwaga wa merafe ye mengwe ya Bibele - Mojalefa, Mawatle J. (Verbum et ecclesia, 2011)
The Pedi year: A comparison with the year of the other biblical nations The investigation grounds arguments on facts that there is correlation between Sepedi and Hebrew calendars particularly in relation to similarity as well as difference between the two nations’ beliefs which are related to the number (twelve months) of the months of the year. This means that Sepedi and Hebrew believe that the year comprised twelve months. Adding to this, the four Hebrew’s early names of the months of the year, namely Abib, Ziv, Ethanim and Bul, of uncertain meaning, differ from the contemporary Hebrew calendar months. This featuristic phenomenon appears also in the Sepedi naming of the months of the year where a month is named after two or more names, such as Dibokwane (February), Hlakola (March), Mopitlo (May), Phupu (June) and Ngwatobošego (June) as well as Mosegamanye (July). The arrangement of the months of the year brings forth certain similarity to the two calendars of these two languages. However, there is difference between the two calendars in relation to the number of the days of the week.